COMPARISON OF GIVING MIND MAP AS A RECITATION AND GIVING QUESTION THAT START TALKING STICK LEARNING COOPERATIVE MODEL TO BIOLOGY COMPETENCIES - Dian Novika Permatasari; Rahmadhani Fitri; Ganda Hijrah Selaras; Syamsurizal Syamsurizal (ATRIUM PENDIDIKAN BIOLOGI, 2021)
The problem at SMPN 3 Padang Panjang is the low level of student learning competencies including knowledge, attitudes, and skills. Efforts that can be done are applying giving recitation in the form of mind mapping with giving questions that start cooperative learning model talking stick to student biology learning competencies. This type of research is a experimental research design, namely the The Statis Group Comparison Design. The population in the study of all students of class VII SMPN 3 Padang Panjang who were enrolled in the 2018/2019 Academic Year grouped in 7 classes. Sampling used purposive sampling technique. Based on the results of the study using the t-test on the competency of students' knowledge the value of tcount was 1,69>1.67 ttable, and the competency skill of the experimental class 1 is 80%  with very good categories while the experimental class II are  76 % with good categories. In the attitude competence of the experimental class 1 is 85%  are good categories while the experimental class II are 81% with sufficient categories. This shows that the hypothesis is accepted in the competence of knowledge, attitudes and skills. The conclusion of the study ,there is a difference in giving recitation in the form of mind mapping with the provision of questions that initiate cooperative learning the talking stick model to biology learning competencies in the realm of knowledge, attitudes and skills in class VII of SMPN 3 Padang Panjang.